PENGARUH REWARD DAN PUNISHMENT TERHADAP MOTIVASI KERJA KARYAWAN PADA PT DERAYA - Nesia Nanda Kurnia (2021)
This research is a quantitative study with the aim of knowing and proving the effect of reward and punishment on the work motivation of PT Deraya employees. The population and sample used in this study were 65 employees at PT Deraya. In testing data with Smart PLS 3.0. The results showed that (1) Reward had a significant positive effect on Work Motivation, and (2) Punishment had a significant positive effect on Work Motivation.